Peer to peer lending and financial inclusion in Brazil: a case study - Lilienthal, Julian Friedrich (2016)
While pursuing the objective to investigate the potential for the P2P innovation to enhance financial inclusion in Brazil, the P2P industry and the current market environment were analyzed in order to highlight the factors that can facilitate this desired enhancement. There seems to be no doubt that there is substantial potential for the P2P industry worldwide and in Brazil but, beyond this, a considerable part of this industry could be providing financially inclusive products. The P2P industry in Brazil needs to recognize the potential for growing, not only the industry itself, but also the market for financially inclusive P2P products. The first section of this thesis focuses on financial inclusion briefly in order to establish the frame of what is being addressed. Subsequently the P2P industry is analyzed globally, locally in Brazil and with regard to financial inclusion. The study is conducted through an interview with the founder of a P2P platform in Brazil and its data collection is used to build a case study which allowed for an analysis of the potential for financial inclusion of the P2P industry and the development of key success factors with regard to converting this potential into results.